PEDAGOGICAL CONDITIONS FOR THE FORMATION OF HYPOTHETICAL THINKING IN FUTURE BACHELORS OF TECHNICAL DIRECTIONS - Khujakulov Anvar Karomatullo o‘g‘li (American Journals, 2024)
This article presents the theoretical justification for the selection of pedagogical conditions that, in our opinion, contribute to the effective formation of hypothetical thinking in future bachelors of technical directions of education.
Keywords: Hypothetical thinking, pedagogical conditions, future bachelors, interactive teaching, axiological approach, etc.